Sprifermin: Effects on Cartilage Homeostasis and Therapeutic Prospects in Cartilage-Related Diseases - Song, Zongmian; Li, Yusheng; Shang, Chunfeng; Shang, Guowei; Kou, Hongwei; Li, Jinfeng; Chen, Songfeng; Liu, Hongjian (Frontiers in Cell and Developmental Biology, 2021)
When suffering from osteoarthritis (OA), articular cartilage homeostasis is out of balance and the living quality declines. The treatment of knee OA has always been an unsolved problem in the world. At present, symptomatic treatment is mainly adopted for OA. Drug therapy is mainly used to relieve pain symptoms, but often accompanied with adverse reactions; surgical treatment involves the problem of poor integration between the repaired or transplanted tissues and the natural cartilage, leading to the failure of repair. Biotherapy which aims to promote cartilage in situ regeneration and to restore endochondral homeostasis is expected to be an effective method for the prevention and treatment of OA. Disease modifying osteoarthritis drugs (DMOADs) are intended for targeted treatment of OA. The DMOADs prevent excessive destruction of articular cartilage through anti-catabolism and stimulate tissue regeneration via excitoanabolic effects. Sprifermin (recombinant human FGF18, rhFGF18) is an effective DMOAD, which can not only promote the proliferation of articular chondrocyte and the synthesis of extracellular matrix, increase the thickness of cartilage in a dose-dependent manner, but also inhibit the activity of proteolytic enzymes and remarkedly slow down the degeneration of cartilage. This paper reviews the unique advantages of Sprifermin in repairing cartilage injury and improving cartilage homeostasis, aiming to provide an important strategy for the effective prevention and treatment of cartilage injury-related diseases.